PENGARUH KOMPETENSI, INDEPENDENSI, DAN MOTIVASI TERHADAP KUALITAS AUDIT - Sinambela, Tongam (Feb Universitas Dirgantara Marsekal Suryadarma, 2019)
This study aims to examine the influence of competence, independence and motivation on audit quality. A common problem in this study is that audit findings are not detected by the inspectorate apparatus as internal auditors, but are found by an external auditor, the Supreme Audit Agency (BPK). Data were analyzed using Structural Equation Modeling (SEM) with SPSS 23 and Lisrel 8.80 applications.The results of this study indicate that competence has a positive and significant effect on audit quality as well as motivation variable does. Meanwhile independence has no positive effect on Audit Quality. The value of coefficient of determination shows that together the competence, independence and motivation variables contribute to the audit quality variable of 84%, while the remaining 16% is influenced by other variables outside the model